Pengaruh Experiential Marketing terhadap Minat Beli Ulang dan Word Of Mouth dengan Customer Satisfaction sebagai Variabel Intervening ( Studi Kasus Legend Coffee Yogyakarta ) - Suyetno suyetno suyetno (Program Studi Manajemen Fakultas Ekonomi UST, 2019)
The purpose of this study was to study the Analysis of the Effect of Experiential Marketing on Repurchase Interest and Word of Mouth with Customer Satisfaction as an intervening variable (Case Study of Legend Coffee Yogyakarta) This research is a quantitative research. The sample in this study is consumers who shop at Legend Coffee Yogyakarta with a minimum of two times. Data collection was carried out using a questionnaire or questionnaire method. Data analysis technique used is a regression technique that is supported by the t test and classical assumptions, the data obtained were processed using SPSS 21. The results of this study indicate that Experiential Marketing has a positive and significant effect on Customer Satisfaction, Eperiential Marketing has a positive and significant effect on Repurchase Interest and Word of Mouth, Customer Satisfaction has a positive and significant effect on Repurchase Interest and Word of Mouth.